HUBUNGAN USIA IBU DAN PARITAS DENGAN GEJALA DEPRESI PADA KEHAMILAN - Risky Puji Wulandari; Perwitasari Perwitasari (Journal of Midwifery and Reproduction, 2021)
Depression is the most common mental disorder during pregnancy period, which may persist to be postpartum depression if the symptoms are not well managed. Not only this problem negatively effect on maternal health but also child outcomes. The aim of this study was to examine the association of depressive symptoms among pregnant women with mother age and parity. An analytic descriptive study with cross sectional approach among 60 women in last trimester (38-41 weeks) was conducted. Samples were recruited using consecutive sampling technique from the data registered in four community health centers in Magelang Regency. Data were collected by administering sociodemographic questionnaire AND EPDS and analyzed using chi-squre test with SPSS software 20. Prevalence of drepressive symptoms during pregnancy was at 25% with EPDS scores ≥10. Statistical measure using bivariate analysis showed there was significant correlation between age, parity and depressive symptoms, p value 0,039 (p>0,05 and 0,016 (p>0,05, respectively. Effort related to improving maternal mental health may target risk factor such as age and parity as a strategy of promotion and prevention thus healthy and quality of future generation could be actualized. Considering these significant factor for delivering psychological care is essential to meet mother’s need.